(untitled) (World Bulletin of Public Health, 2024)
The article presents the results of studying the concepts, knowledge and skills of students of an educational institution about a healthy lifestyle. Despite the fact that students have a healthy lifestyle knowledge, 44.5% do not follow it. One of the factors that determine human health is lifestyle, the proportion of which is 50-60%. Therefore, the formation of healthy lifestyle skills in young people is important in the Prevention of various chronic diseases in the future.